2013
DOI: 10.1093/trstmh/trs024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C infection among children with  -thalassaemia major in Mid Delta, Egypt: a single centre study

Abstract: HCV infection is highly prevalent in children with β-TM in Egypt despite strict pre-transfusion blood testing. This should arouse the attention for environmental and community acquired factors. Quality management to insure infection control in minor operative procedures and adding more sensitive tests for blood screening are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…This coincides with previous reports,4,12 but contradicts others 3,14,16–18. Gender does not seem a risk factor for acquiring TTI, but was unexpectedly associated with HCV seropositivity in our study; this finding was also reported elsewhere 19.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This coincides with previous reports,4,12 but contradicts others 3,14,16–18. Gender does not seem a risk factor for acquiring TTI, but was unexpectedly associated with HCV seropositivity in our study; this finding was also reported elsewhere 19.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, anti-HCV seropositivity in our patients (11.32%) was lower than those reported among multitransfused patients in Jordan (40%),2 Egypt (45% to 76%),4,15 Iran (44.7%),16 India (16% to 26%)5 and Pakistan (51.3%),17 which is reflected by the relatively lower prevalence (0.95%) of HCV seropositivity among Syrian blood donors 8…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Sharing razors (83,84), sharp objects (nail clippers, manicure cutters, scissors) (83), tooth brush (85), non-sharp objects (shower scrapper, towels, combs) (48,(86)(87)(88), and some folk medical practices including cupping/ventosed bloodletting (known in the Arab world as hijama) (37,(89)(90)(91), circumcision and ritual clitorodectomy (36,41,69,76,92) were studied as risk factors for HCV infection only in the late 1990s. Similarly, the role of barber was only addressed during the last decade.…”
Section: Discussionmentioning
confidence: 99%